Our Native Land: First Nations Constitutional Conference - Bernelda Wheeler (Host); Lee Quimo? (Performer); Bernelda Wheeler (Reporter); Dove Cuthand? (Speaker); Pierre Trudeau (Speaker); Noel Starblanket (Speaker); Joe Dionne (Interviewee); Robert Manuel (Speaker); John Munroe (Speaker); George Manuel (Speaker); Ann Roberts (Reporter); Shotbothsides (Speaker); et al. (CBC, 1980)
Introduction / Bernelda Wheeler. -- [Unknown Song] / Lee [Quimo?]. -- News reports / Bernelda Wheeler. -- Speech / [Dove Cuthand?]. -- Speech / Prime Minister Pierre Trudeau. -- Statement / Noel Starblanket. -- Interview / Joe Dionne. -- Statement / Noel Starblanket. -- Statement / Chief Robert Manuel. -- Statement / John Munroe. -- Statement / George Manuel. -- Introduction / Bernelda Wheeler. -- News reports / Ann Roberts. -- News reports / Bernelda Wheeler. -- Statement / Chief Shotbothsides. -- Statement / Prime Minister Pierre Trudeau. -- Statement / Robert Manuel. -- Statement / Noel Starblanket. -- News Report / Gary George. -- [Untitled song] / Winston Whatney. Item consists of an audio recording of the radio show, "Our Native Land", hosted by Bernelda Wheeler. It opens with an unknown song by Lee [Quimo?] and then Bernelda Wheeler begins news coverage of the First Nations Constitutional Conference. It includes several speeches and statements, each of which she makes an introduction to. The first speech comes from [Dove Cuthand??] on political rights. Next is a speech from Prime Minister Pierre Trudeau and a statement from the president of the National Indian Brotherhood, Noel Starblanket, in response. This is followed by an interview with Joe Dionne on the resolution made at the conference to have an official Indian government made up of an assmbly of chiefs, and a response to this idea by Noel Starblanket. After this is Chief Robert Manuel's statement on the constitutional powers that should be held by this assembly. This is followed by a statement from the Indian Affairs Minister, John Munroe, on revising the Indian Act, with a response from George Manuel, of the Union of British Columbia Indian Chiefs. Next in the program is a news report by Ann Roberts on a federal inquiry into healthcare in Alert Bay on the west coast, following a short introduction to the segment by Bernelda Wheeler. Bernelda Wheeler then returns to coverage of the conference. Next is a statement from Chief Shotbothsides on ...